To what extent can restorative justice be applied in murder cases involving children under Article 340 of the Criminal Code or Article 338 of the Criminal Code in conjunction with Article 55 of the Criminal Code? A case study of the murder of a child in Subang with Subang District Court Decision Number 1/Pid.Sus-Anak/2025/PN Sng - Priyana, Yana; Purba, Tumian Lian Daya (West Science Law and Human Rights, 2025)
This paper examines the application of restorative justice in cases of juvenile homicide under Indonesian law, focusing specifically on a case study involving the murder of a child in Subang, as reviewed in Subang District Court Decision Number 1/Pid.Sus-Anak/2025/PN Sng. The study uses a normative juridical approach to analyze the feasibility of applying restorative justice principles in such serious criminal cases, particularly those involving minors. The Indonesian Criminal Code (KUHP), Law on the Juvenile Court (UUPA), and restorative justice frameworks are explored in relation to the case. The paper discusses the role of the offender's age, mental state, and the victim’s family's involvement in the restorative process, highlighting both the potential benefits and challenges of implementing restorative justice in juvenile homicide cases. The findings suggest that while restorative justice can be a rehabilitative tool for juvenile offenders, its application in cases involving serious offenses like murder is complex and requires careful consideration of the emotional impact on the victim’s family, the offender’s potential for reform, and societal expectations for justice. The paper concludes by recommending further exploration of restorative justice as part of broader juvenile justice reforms in Indonesia.